Quality Assessment of 25(OH)D, Insulin, Total Cholesterol, Triglycerides, and Potassium in 40-Year-Old Frozen Serum. (15th February 2015) - Leu, Monica; Mehlig, Kirsten; Hunsberger, Monica; Torinsson Naluai, Åsa; Blennow, Kaj; Zetterberg, Henrik; Björkelund, Cecilia; Lissner, Lauren
Abstract : Background. Many longitudinal epidemiological studies collect specimens into biobanks to investigate how biomarkers predict future disease. In 1968-1969, the Population Study of Women in Gothenburg (PSWG) established a biobank of serum samples. Objective. To examine the validity of 25-hydroxyvitamin D (25(OH)D), total cholesterol, triglycerides, insulin, and potassium after 40 years of storage at −20°C in terms of relative and absolute agreement. The quality of these markers under such condition has not been previously investigated. Methods. Baseline and remeasured levels were compared in selected samples through percentage change, correlation, and regression. 25(OH)D levels, not assessed at baseline, were compared by season, by BMI, and longitudinally over six years. Results. Despite some lack of absolute agreement, Spearman correlations were >0.7 and statistically significant for all biomarkers. The 1968-1969 25(OH)D correlated with BMI( r = - 0.45,   P = 0.05 ) and with levels six years later( r = 0.85,   P < 0.001 ) . Summer 25(OH)D was higher than winter 25(OH)D( P = 0.02 ) . Conclusion. For all markers, baseline and remeasured levels exhibited high relative agreement. 25(OH)D was comparable with expected levels on fresh blood and varied with season. In future studies, PSWG individuals will be ranked according to these markers in order to predict incidence of disease.